Investigation of the Use of Energy Efficient Bulbs in Residential Buildings in Ile-Ife, Osun State, NigeriaInvestigation of the Use of Energy Efficient Bulbs in Residential Buildings in Ile-Ife, Osun State, Nigeria (International Journal of Built Environment and Sustainability, 2018)
The use of incandescent bulbs by the majority of building occupants in Nigeria has complemented high cost of electrical energy consumption and this has informed prevalence of different types of energy efficient lighting bulbs. The study, therefore, identified and examined types of lighting bulbs used, assessed the rate of use of energy efficient bulbs in selected residential buildings and examined factors influencing its use. The study was carried out in Ife Central Local Government Area of Osun State, Nigeria. Residential settlements in core wards in the study area were considered and four wards in the core zone of the Local Government were randomly selected from the total of eleven while data collection was done with the use of primary and secondary data techniques. Simple random sampling technique was used to select 5% sample size from the entire population and systematic sampling procedure was further employed by selecting every 10th building in the direction of movement which indicated selection of 123 houses. A total of 123 structured questionnaires were administered on the respondents on issues associated with the use of lighting bulbs. Data collected were analysed by both descriptive and inferential statistical techniques. The study found that 90.53% and 72.63% of the respondents used incandescent and energy saving bulbs respectively; variation existed in the wattages of different brands of energy saving and non-energy saving bulbs used in the selected buildings: A major proportion of the respondents used an average number of 1-5 lighting bulbs in buildings and its spaces therein; while quality and cost-saving benefit, energy saving benefit and durability of bulb influenced the choice of fluorescent tubes, compact fluorescent bulbs and light emitting diodes with a mean score value of 2.20, 2.29 and 2.85 respectively. In view of the need to enhance visual performance and comfort of buildings and its occupants respectively, efforts must be made by government to ensure that consumers awareness and enlightenment be increased on the types of lighting bulbs to procure and there is also need to strengthen mechanisms through the importation and sales of energy efficient bulbs only so as to enhance its cost-saving and environment–related benefits amongst others.
Keywords: Buildings; Electrical supply; Energy; Lighting bulbs; Management; Occupants; Spaces